The Effects of Tax Sanctions, Taxpayer Awareness, and Tax Understanding MSME on Tax Compliance: The Moderating Role of Risk Preference - Yuliani, Sinsin Putri; Sistalia, Tri Ayu; Yulianto, Agung (Yayasan Ilomata, 2024)
This study's objective was to assess and examine the impacts of tax penalties, taxpayer awareness, and taxation comprehension on the tax compliance of micro, small, and medium-sized businesses (SMEs) in Cirebon City, with risk preference moderating variables. The method used in this research is quantitative, and the type of data used is primary data obtained from 250 respondents. This study shows that tax sanctions, taxpayer awareness, increasing taxpayer compliance, and understanding of taxation affect taxpayer compliance. Risk preferences do not strengthen the relationship between taxpayer awareness and taxpayer compliance, and risk preferences do not moderate the knowledge of taxation with taxpayer compliance. The Directorate General of Taxes can use this study to encourage a stronger tax approach and understanding of taxation, especially for Cirebon City micro, small, and medium-sized businesses (SMEs).